Mycobacterium avium complex and Cryptococcus neoformans co-infection in a patient with acquired immunodeficiency syndrome: a case report. Issue 3 (4th May 2022) - Gregoire, Emilien; Pirotte, Benoit François; Moerman, Filip; Altdorfer, Antoine; Gaspard, Laura; Firre, Eric; Moonen, Martial; Darcis, Gilles
ABSTRACT: Introduction: Opportunistic infections (OI) are common in patients with acquired immunodeficiency syndrome (AIDS). Cryptococcus neoformans and Mycobacterium avium complex (MAC) are frequently responsible of such infections. However, concurrent infection with these two pathogens is uncommon and underreported in the literature. Case description: We describe the case of a 28-year-old Caucasian Belgian patient with no travel history, who presented with low-grade fever, headache and wasting syndrome. He was diagnosed with human immunodeficiency virus (HIV) infection at AIDS stage, with a HIV viral load of 506, 000 viral copies/mL and a CD4 + T-cells count of 10 cells/µL. Diagnosis of disseminated Cryptococcus neoformans infection was made by positive serum cryptococcal antigen and positive culture for Cryptococcus neoformans in blood and in cerebrospinal fluid. Diagnosis of disseminated Mycobacterium avium complex infection was made by positive culture on a biopsy of a mediastinal lymph node. With adequate anti-retroviral therapy (ART) and treatment of these OIs, the patient recovered well and had a good clinical evolution. Discussion and conclusion: To our knowledge, this is the second case of coexistence of these two dangerous OIs reported in the post ART era. Clinicians should be aware that such co-infections still happen in high-income countries, in patients with severe immunodeficiency. Early detection and treatment of HIV is of paramount importance to prevent AIDS and its complications. We highlight the importance of thoroughly excluding all opportunistic infections in patients with newly diagnosed AIDS. Abbreviations: ABC: abacavir; AIDS: acquired immunodeficiency syndrome; AFB: acid-fast bacilli; ART: antiretroviral therapy; CM: cryptococcal meningitis; CrAg: cryptococcal antigen; CSF: cerebrospinal fluid; CT: computed tomography; EACS: European AIDS Clinical Society; FTC: emtricitabine; HIC: high-income countries; HIV: human immunodeficiency virus; HIV-VL: HIV-viral load; ICP: intracranial pressure; IRIS: immune reconstitution inflammatory syndrome; MAC: Mycobacterium avium complex; MRI: magnetic resonance imaging; MSM: man who has sex with men; NR: normal range; OD: omne in die = once daily; OI: opportunistic infection; RAL: raltegravir; TAF: tenofovir alafenamide fumarate